Implementasi Pendidikan Karakter dalam Pembelajaran PAI di SDIT Ummul Qur’an Gebang, Kabupaten Langkat. - Fahri Agung Nasution; Pauli Anggraini; Nur Atika; Hasnan Abdi; Najaruddin Butar-Butar; Nirwana Anas (Jurnal Dirosah Islamiyah, 2023)
Teacher Professionalism is something that cannot be negotiated, including for a figh teacher. Because the professionalism of a teacher plays a very dominant role, event thought the sophistication of technologi is veryimpersive. there are still too many human elements such as attitudes, values systems, feelings, motivation, habits, etc. which are expected to be the result of the learning process. A good religious attitude is one of the hopes that results from a fight study. And only figh learning managed by a professionalfigh teacher has implications for the formation of students’ religious attitudes. Professional figh teachers are able to create a dynamic and democratic learning atmosphere, and will have implications for students’ religious attitudes in the from of; first, the students will understand what they do and at the same time understand what the other people who are different from it have been practicing. Second, the level of student obedience in carrying out religious rites is getting better. Third, the more students have more confidence in the thurth of their religion, fourth, the students’ commitment to godliness is getting better, good, and fith, embedded tolerance towards all differences. Keywords: Teacher Professionalism, religious attitudes